A Novel Azaphilone Muyophilone A From the Endophytic Fungus Muyocopron laterale 0307-2 - Yuan, Chao; Guo, Yuhua; Wang, Ke; Wang, Zhunian; Li, Longfei; Zhu, Huajie; Li, Gang (Frontiers in Chemistry, 2021)
Two known azaphilone derivatives, 4,6-dimethylcurvulinic acid (1) and austdiol (2), and their novel heterotrimer, muyophilone A (3), were isolated and identified from an endophytic fungus, Muyocopron laterale 0307-2. Their structures and stereochemistry were established by extensive spectroscopic analyses including HRMS, NMR spectroscopy, electronic circular dichroism (ECD) and vibrational circular dichroism (VCD) spectroscopic methods, as well as single crystal X-ray diffraction. In the structure of 3, two compound 2-derived azaphilone units were connected through an unprecedented five-membered carbon bridge which was proposed to be originated from compound 1. Compound 3 represents the first example of azaphilone heterotrimers.